ADMINISTRASI DESA ONLINE DESA NOGOSARI KECAMATAN NGADIROJO KABUPATEN PACITAN - Djoko Sasono; Agus Darwanto; Ir Supardi, Msc (JPM17: Jurnal Pengabdian Masyarakat, 2016)
The village administration is a key point that must be owned by the villageso the village government can run well. Nogosari own village VillageAdministrative own. Problems faced Village Nogosari is to increase services torural communities that activity of the village government more quickly serve thewhole village Nogosari, a good start for reporting, query correspondence,harvest activities, activities of SMEs and others can be served, monitored andcontrolled more to fast and more accurate. With the online system thenChairman of BPD can oversee the work plans that will be implemented VillageHead, and when the Chairman of the BPD approve these plans, the Chairmanof BPD can activate work plans the chief. When the village chief work plan hasnot been activated, then it means that the work plan are yet to be implemented.Work in progress and already implemented can also be monitored by thechairman of the BPD, so if at the time of execution of the job is not inaccordance with prior planning, it can be known by the chairman of the BPDand can immediately take the steps necessary to anticipate this, Seeing theproblems it is through science and technology program for People (IbM)proposed making SistemAdministrasi village in the village Nogosari NgadirojoPacitan using Information Technology program.Keyword: System IT Administrasi Village, .............. The potential, profileadministration, activation of BPD, correspondence